Strategi Pengelolaan Sampah Rumah Tangga Di Kecamatan Senapelan Kota Pekanbaru - Putri Kalbina; Sukendi Sukendi; Yusni Ikhwan Siregar (Jurnal Zona, 2023)
Household waste which is often the most waste generated every day, remains of human daily activities in solid form at the household scale. The lack of public attention to environmental cleanliness, especially waste management, results in accumulation and even non-optimal waste management, couses accumulation and even waste management that is not optimal. To achieve success in development, it is necessary to payattention, one of which is community involvement in waste management. The conditions in the field clearly show that Senapelan Subdistrict itself carries out waste disposal independently, garbage has accumulated at several points causing an unpleasant odor, and even illegal TPS have appeard at several points. This research was conducted from May to September 2022 in Senapelan District using a descriptive survey method through interviews and distribution of questionnaires, literature searches and field observations. This study aims to formulate a household waste management strategy in Senapelan District using SWOT analysis. The selected household waste management strategy based on the results of a SWOT analysis which shows superiority in the strengths and opportunities that exist in Senapelan District is optimizing DAK funding for waste management and sanitation facilities, increasing human resources to support waste management, improving the waste recycling process so that it is reduced the amount of existing waste, increasing communication media or socializing to the community the importance of household waste management.